The appropriation of oral/spoken French by L2 learners: Variational features and educational perspectives - Paternostro, Roberto (Scandinavian Studies in Language, 2023)
The expressions ‘oral French’ and ‘spoken French’ are often used as equivalents. However, they have implications that are far from trivial, especially when it comes to teaching the French language. In this article, we will attempt to point out the nuances behind the expressions oral and spoken French, through reflections on the diamesic and the diaphasic variational dimensions. Secondly, we shall present the implications that this perspective may entail when it comes to the teaching of French as a foreign language (FLE). This research on the teaching of spoken French will also allow us to take into consideration some issues and challenges in relation to the implementation of a ‘didactics of spoken French’. The presentation of examples from the fieldwork research will enable us to dig further into these questions.